2014
DOI: 10.12688/f1000research.3718.1
|View full text |Cite
|
Sign up to set email alerts
|

Role of bacteriophages in STEC infections: new implications for the design of prophylactic and treatment approaches

Abstract: Shiga toxin (Stx) is considered the main virulence factor in Shiga toxin-producing Escherichia coli (STEC) infections. Previously we reported the expression of biologically active Stx by eukaryotic cells in vitro and in vivo following transfection with plasmids encoding Stx under control of the native bacterial promoter. Since stx genes are present in the genome of lysogenic bacteriophages, here we evaluated the relevance of bacteriophages during STEC infection. We used the non-pathogenic E. coli K12 strain ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 11 publications
1
12
0
2
Order By: Relevance
“…Therapeutic use of certain antibiotics is known to induce Stx 2a phages (Huang et al, 1987;Mead and Griffin, 1998;Zhang et al, 2000;Zimmerhackl, 2000;Wong and Brandt, 2002;McGannon et al, 2010;Wong et al, 2012;Amorim et al, 2014;Rahal et al, 2015). Strains were cured of stx by inducing the Stx-phages with Mitomycin C (MMC), a potent Stx 2a phage inducing agent that triggers the RecA-mediated SOS-response (Fuchs et al, 1999;Kimmitt et al, 2000;Los et al, 2009;Imamovic and Muniesa, 2012).…”
Section: Laboratory Isolation Of Stx-cured Ehec O157:h7mentioning
confidence: 99%
“…Therapeutic use of certain antibiotics is known to induce Stx 2a phages (Huang et al, 1987;Mead and Griffin, 1998;Zhang et al, 2000;Zimmerhackl, 2000;Wong and Brandt, 2002;McGannon et al, 2010;Wong et al, 2012;Amorim et al, 2014;Rahal et al, 2015). Strains were cured of stx by inducing the Stx-phages with Mitomycin C (MMC), a potent Stx 2a phage inducing agent that triggers the RecA-mediated SOS-response (Fuchs et al, 1999;Kimmitt et al, 2000;Los et al, 2009;Imamovic and Muniesa, 2012).…”
Section: Laboratory Isolation Of Stx-cured Ehec O157:h7mentioning
confidence: 99%
“…Stx phages play an important role in disease, STEC evolution and ecological fitness. Synthesis and secretion of these toxins, particularly Stx2 type, are coupled with the lytic cycle of such phages whose direct role in disease pathogenesis has been also proposed (Amorim et al, ). Additionally, toxin production can be amplified by the horizontal transfer of Stx phages to commensal E. coli (Gamage et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously observed a dramatical decrease of GFP expression in vivo in mice treated with chitosan after infection with a non-pathogenic E. coli strain containing a mutant bacteriophage in which the gene of stx was replaced by gfp sequence (Amorim et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we showed that chitosan has anti-bacteriophage activity in vitro and in vivo (Amorim et al, 2014 ). Chitosan is a cationic linear polysaccharide polymer obtained after the deacetylation of chitin; this polymer has been widely-used as an antimicrobial agent against several microorganisms (Kong et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation